2012
DOI: 10.1111/j.1365-2958.2012.08124.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucomutase is absent in Trypanosoma brucei and redundantly substituted by phosphomannomutase and phospho‐N‐acetylglucosamine mutase

Abstract: The enzymes phosphomannomutase (PMM), phospho-N-acetylglucosamine mutase (PAGM) and phosphoglucomutase (PGM) reversibly catalyse the transfer of phosphate between the C6 and C1 hydroxyl groups of mannose, N-acetylglucosamine and glucose respectively. Although genes for a candidate PMM and a PAGM enzymes have been found in the Trypanosoma brucei genome, there is, surprisingly, no candidate gene for PGM. The TbPMM and TbPAGM genes were cloned and expressed in Escherichia coli and the TbPMM enzyme was crystallize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 78 publications
(138 reference statements)
1
31
0
1
Order By: Relevance
“…This can make them more difficult to identify as a member of the superfamily based on sequence searches. The sequence motif of the sugar-binding loop in the PAGMs is distinct: –FEANG– (Bandini et al, 2012; Kato et al, 2005) (Table 1 and Fig. 2), with the asparagine reflecting a role in recognizing the N -acetyl group of the 1-phospho form of the sugar (Nishitani et al, 2006).…”
Section: Biologymentioning
confidence: 99%
“…This can make them more difficult to identify as a member of the superfamily based on sequence searches. The sequence motif of the sugar-binding loop in the PAGMs is distinct: –FEANG– (Bandini et al, 2012; Kato et al, 2005) (Table 1 and Fig. 2), with the asparagine reflecting a role in recognizing the N -acetyl group of the 1-phospho form of the sugar (Nishitani et al, 2006).…”
Section: Biologymentioning
confidence: 99%
“…Indeed, it was demonstrated that PAGM is capable of replacing PGM in T. brucei (Bandini et al. ). Galactose is essential for T. brucei , but the parasite not only lacks transporters for its uptake, but also a gene for galactokinase.…”
Section: Observations and Predictionsmentioning
confidence: 99%
“…PGM may be replaced by phospho-N-acetylglucosamine mutase (PAGM), which reversibly catalyzes the transfer of phosphate between the C6 and C1 hydroxyl groups of Nacetylglucosamine, mannose, glucose, and phospho-Nacetylglucosamine. Indeed, it was demonstrated that PAGM is capable of replacing PGM in T. brucei (Bandini et al 2012). Galactose is essential for T. brucei, but the parasite not only lacks transporters for its uptake, but also a gene for galactokinase.…”
Section: Other Enzymes Of Carbohydrate Metabolismmentioning
confidence: 99%
“…These additional enzymes involved in the metabolism of sugars might indicate a higher metabolic flexibility of L. tarentolae compared to African trypanosomes. In T. brucei , the phosphomannomutase Tb927.10.6440 was found in the glycosome, where it can act as phosphoglucomutase during glycolysis 36 . T. brucei phospho-N-acetylglucosamine mutase (Tb927.8.980) was also partially glycosomal 36 .…”
Section: Resultsmentioning
confidence: 99%
“…In T. brucei , the phosphomannomutase Tb927.10.6440 was found in the glycosome, where it can act as phosphoglucomutase during glycolysis 36 . T. brucei phospho-N-acetylglucosamine mutase (Tb927.8.980) was also partially glycosomal 36 . Neither has an obvious PTS1 targeting signal so it is possible that they have either an internal glycosomal targeting signal or that they are co-imported via association with other glycosomal targeting signal-containing proteins 37, 38 .…”
Section: Resultsmentioning
confidence: 99%